2020
DOI: 10.1080/00365521.2020.1774923
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peritumoral SPARC during distal cholangiocarcinoma progression and correlation with outcome

Abstract: Objectives: Distal cholangiocarcinoma (dCCA) is a malignancy with a dismal prognosis. One of the hallmarks is the presence of a rich desmoplastic stroma believed to contribute to tumor progression and treatment resistance. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein implicated in tumor-stroma interaction with prognostic correlation across several malignancies. The aim of the present study was to evaluate the expression pattern and prognostic significance of SPARC in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…and Deng et al [29,30]. In addition, we first discovered that knockdown of SPARC inhibited the M2 polarization of macrophages.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…and Deng et al [29,30]. In addition, we first discovered that knockdown of SPARC inhibited the M2 polarization of macrophages.…”
Section: Discussionmentioning
confidence: 81%
“…According to Johannes et al, the abundance of SPARC is heightened in the distal CCA, which was linked with lymph node metastasis [29]. In addition, Deng et al confirmed that the SPARC content is increased in CCA tissues and cells, and SPARC elevated CCA cell proliferation, metastasis, and EMT [30].…”
Section: Discussionmentioning
confidence: 99%
“…All samples underwent histopathological reevaluation by an experienced gastrointestinal pathologist (A.S) blinded to the original assessment. The cohort has been previously described [23,24]. Staging was based on the American Joint Committee on Cancer (AJCC) 7th edition [5].…”
Section: Study Populationmentioning
confidence: 99%